Investigating the electrical conductivity of PMMA/ carbon black and of PS/PMMA/ carbon black blends prior to and after shear - Voigt, Monika; Pan, Yamin; Liu, Xian Hu; Schubert, Dirk W. (Book of Abstracts, 2016)
The electrical conductivity of disk-like poly(methyl methacrylate)/carbon black (PMMA/CB) composite samples with   various CB concentrations as a function of the position was investigated prior to and after a shear process. Novel   electrical conductivity maps of the samples were obtained. It was found that the electrical conductivity from angular   averaging of static samples is independent of the radius regardless of the CB concentrations but strongly   dependent for sheared samples with varied CB concentrations. 1 Additionally, CB filled polystyrene (PS) and PMMA   blends with different PS/PMMA ratio have been fabricated by melt blending to obtain conductive polymer   composites with a low electrical percolation threshold. The electrical conductivity of the composites was highest   when PS and PMMA phases form a co-continuous structure and CB particles were selectively located and   percolated in the PS phase. Moreover, the simultaneous evolution of electrical conductivity and phase morphology   of CB filled co-continuous PS/PMMA (50v/50v) composites was investigated under shear and quiescent melt.   Under shear stress, the conductivity of these blends decreased by about two orders of magnitude and the phase   morphology changed into a strip structure 2 . Impact of shear on the phase morphology become less significant as   CB concentration increased or shear stress decreased. During subsequent recovery, pronounced phase structure   coarsening and conductivity increase were observed in the systems. The results obtained in this study provide a   deeper insight into phase structural and conductivity changes in conductive polymer composite induced by shear   deformation.   1. X. Liu, J. Krückel, G.Q. Zheng, D.W. Schubert, ACS Appl. Mater. Interfaces 2013, 5, 8857   2. Y. Pan, X. Liu, X. Hao, Z. Starý, D.W. Schubert, Europ. Polym. J. 78 (2016) 106–115